KAP Survey: Does It Really Measure Knowledge, Attitudes and Practices? - Patel, Prakash (National Journal of Community Medicine, 2022)
Knowledge, attitude, and practice (KAP) surveys are widely used to gather information from people in India as well as in other countries. However, there is rarely any discussion about the usefulness of KAP surveys and various challenges of conducting surveys and interpretation of results in different settings. The purpose of this article is to highlight the use of KAP surveys in understanding and researching health-related knowledge, attitudes, and behaviours, as well as to identify some of the primary obstacles that KAP surveys face.